Identification of macroeconomic determinants for diversification and investment strategy for Islamic unit trust funds in Malaysia - Othman, Anwar Hasan Abdullah; Abdul Aziz, Hassanuddeen; Kassim, Salina (Emerald Publisher, 2018)
Purpose – This study aims to investigate the role of selected macroeconomic variables in influencing the movement of Net Asset Value (NAV) of the Islamic Unit Trust Funds (UTFs) in Malaysia. In efforts to arrive at more enriching findings, the UTFs are further categorised into equity, bond, balanced, fixed, mixed, money market and feeder funds. Design/methodology/approach – The study adopts the Vector Autoregression framework (Johansen-Juselius (1990), cointegration test and Vector Error Correction Model to analyse the relationship between the macroeconomic variables and the NAVs of the various type of funds. Findings – The study shows that there is a significant long-run equilibrium relationship between the macroeconomic variables and the NAV of all Islamic UTFs in Malaysia. Despite of this, the findings show that different funds have different responses to the movements of the macroeconomic variables. Practical implications – The results of the study are of significant importance to the various stakeholders in the Islamic UTF industry. Investors benefit in terms of getting the inputs on their investment decisions as to whether to buy, hold or sell fund units within their investment portfolio in the long-run, along with building their optimal portfolio diversification investment strategy, especially in reallocating their assets distribution between the various types of funds in the UTFs industry. For the policy-makers, the findings of the study may assist them in evaluating the suitability of the existing economic policies as to whether they positively or negatively contribute to the development of the Islamic UTFs. Originality/value – This paper fulfils the need to understand how unit-holders can strategise and diversify their portfolio investments in the Malaysian Islamic UTFs industry based on detailed understanding and knowledge derived from rational and scientific inputs.